HASIL BELAJAR IPS TERPADU MODEL TPS DAN NHT DENGAN MEMPERHATIKAN MINAT BELAJAR - Agnestia Refriyona; Pujiati Pujiati; Nurdin Nurdin (FKIP Unila, 2015)
This research aimed to know the difference of IPS learning result and interaction of learning model and learning enthusiasm. Method used was by comparability of experiment approach. Research population were 328 students and the sample were 68 students determined by Cluster Random Sampling. Data collecting was through observation, interview, documentation, test and questionnaire. Hypothesis examination used two ways variant analysis and two independent sampel t-test. The result of this research showed that : (1) There were differences result in IPS learning model of TPS and NHT, ( 2) The learning result of IPS by using TPS model was higher than NHT on high enthusiasm student, (3) The learning result of IPS by using TPS model lower than NHT on low enthusiasm student, (4) There is an interaction between co-operative model with the learning enthusiasm result of IPS using TPS and NHT model, (5) There is an interaction between high and low learning enthusiasm learn to the learning result of IPS using TPS and NHT model.Tujuan penelitian ini untuk mengetahui perbedaan hasil belajar IPS Terpadu serta interaksi model pembelajaran dan minat belajar. Metode yang digunakan komparatif pendekatan eksperimen. Populasi penelitian 328 siswa dan sample 68 siswa ditentukan Cluster Random Sampling. Pengumpulan data melalui observasi, wawancara, dokumentasi, tes dan angket. Pengujian hipotesis menggunakan analisis varian dua jalan dan t-test dua sampel independen. Hasil penelitian menunjukkan : (1) ada perbedaan hasil belajar IPS Terpadu model TPS dan NHT, (2) hasil belajar IPS terpadu model TPS lebih tinggi dibandingkan NHT pada siswa minat tinggi, (3) hasil belajar IPS Terpadu model TPS lebih rendah dibandingkan NHT pada siswa minat rendah, (4) ada interaksi antara model kooperatif dengan minat belajar pada hasil belajar IPS terpadu model TPS dan NHT, (5) ada interaksi antara minat belajar tinggi dan rendah terhadap hasil belajar IPS model TPS dan NHT.Kata kunci: hasil belajar, minat belajar, NHT, TPS